Strategi Pengajaran Pantomim di SMP Negeri 1 Kawali untuk Meningkatkan Kreativitas Siswa dalam Persiapan Kompetisi Pantomim AntarSiswa - Irna Nuraeni; Asep Wasta; Budi Dharma (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The background of this study is based on the absence of formal pantomime learning in the curriculum or in extracurricular activities, but the school is able to achieve achievements in pantomime competitions. This study aims to examine the pantomime teaching strategy at SMPN 1 Kawali in improving student creativity as preparation for facing pantomime competitions between students. This study uses a qualitative descriptive analytical approach with data collection techniques in the form of observation, interviews, documentation and literature studies. The subjects of this study were art and culture teachers and students who were prepared as participants in the pantomime competition. The results of this study indicate that the teaching strategies applied include: (1) Application of a scientific approach and application of the discovery learning method, experimental method, drill method, demonstration method, (2) talent search selection strategy through NMB (Nesaka Mencari Bakat) activities and dance extracurricular activities, (3) competition strategy which includes the stages of introducing basic pantomime concepts, exploring themes and storylines, designing movements and development, intensive training and periodic evaluation of student abilities in terms of expression, movement techniques and creativity. All of these strategies have been proven to be able to improve student creativity, prepare them optimally for competition, and produce achievements in pantomime competitions.